Quality of Service Pengiriman Data dengan Menggunakan Wireless Sensor Network pada Prototype Greenhouse - Budiyarto, Aris; Hadiani, Dini; Ardiyanto, Hery (The Indonesian Journal of Computer Science, 2024)
For agriculture that uses greenhouses, environmental health, especially soil and air, is very important. Therefore, soil and air quality must be managed properly. One way to manage this is by using a wireless sensor network system to facilitate monitoring by greenhouse farmers. This wireless sensor network concept uses NRF24L01+ devices as communication modules and ESP32 as microcontrollers on the master/receiver and 5 nodes/transmitters with each node using DHT22, Soil Moisture Sensor, MH-Z19, MQ-9, and MQ-2 sensors. The focus and purpose of this research is to analyze Quality of Service on wireless sensor network systems with latency/delay test, throughput test, jitter test, packet loss test parameters applied to a greenhouse monitoring system. The final results prove that the performance of the wireless sensor network is very good, so the system can be applied to monitoring environmental quality in greenhouses because the system can work in real-time.